I am homeless if this is not my home - Moore, Lorrie (New York : Alfred A. Knopf, 2023)
A teacher visiting his dying brother in the Bronx. A mysterious journal from the nineteenth century stolen from a boarding house. A therapy clown and an assassin, both presumed dead, but perhaps not dead at all . . . A tragicomic novel about death and devotion.
"This is a Borzoi book."
Keywords: Siblings -- Fiction; Love -- Fiction; Grief -- Fiction; Death -- Fiction; Psychological fiction; Historical fiction; Paranormal fiction